A prospective study of the relationships of autonomy, competence, and relatedness with exercise attendance, adherence, and dropout - Vlachopoulos, S. P.; Neikou, E. (The Journal of Sports Medicine and Physical Fitness, 2007)
Aim: Given the need to investigate determinants of exercise behavior, the study examined the relationship of the needs for autonomy, competence, and relatedness with exercise attendance and adherence/dropout in organized exercise programs over 6 months. A secondary purpose was to further determine the predictive validity of the Basic Psychological Needs in Exercise Scale (BPNES) responses. Methods: A prospective design was utilized where 108 male exercise participants (mean age: 27.38 years) and 120 females (mean age: 27.79 years) completed the BPNES before an exercise class. Six months later, the total number of their visits to the fitness center over the 6-month period was assessed, as well as whether they still attended. Results: Latent variable structural equation modeling demonstrated that it was only the need for competence that significantly predicted exercise attendance and this was the case for both male and female participants, simultaneously. Further, a binary logistic regression demonstrated that only the need for competence predicted group membership among participants who were categorized either as adherers or dropouts. Conclusion: The need for competence emerged as the main predictor of levels of exercise attendance and of exercise adherence/dropout group membership. Moreover, the findings further supported and broadened the validity evidence base of the BPNES responses.